A M68HC11 based digital thermometer - Mohamad Fadhal B Mohamad Asri (2023)
This project is basically aiming not only to build a digital thermometer but also to build fundamental knowledge about interfacing the thermometer hardware and also with the microcontroller M68HC11. Using this project, the measuring temperature system will measure the temperature of water that is between 0 Celsius to 100 Celsius. The output of the measurement will be displayed on the liquid crystal display (LCD). Research methodology basically focuses on how to interface the input and output hardware to the microcontroller.